Beyond happiness : how authentic leaders prioritize purpose and people for growth and impact - Lim, Jenn (Grand Central Publishing, 2021)
Jenn Lim has made a career of helping organizations build workplace cultures that benefit both their employees and their bottom line, with less employee turnover, greater engagement, and higher profits. Her culture consultancy, Delivering Happiness, demonstrates the profound impact happiness can have on businesses' ability to thrive in our ever-changing times. In this book, she shows the way the model works in a hyper-connected fast-paced world, beginning with each individual defining their sense of values and purpose (the ME), and rippling through the organization ecosystem (the WE and the COMMUNITY) in waves of impact.